The Information Users’ Interface Rationalization in Economic Information Systems - Brazaitienė, Tatjana (Ekonomika, 1996)
This paper is concerned with the rationalization of the interactive interface structure in economic information systems (EIS) for decision support. Levels and forms of the dialogue between users and EIS are analysed. The information and model interface is distinguished and discussed.We show peculiarities of the concurrent decision support. Interface rationalization facilities are described: system regulation by an information communication graph; users’ remote work; limited masking of modelling; quasi-information engine.The main results are the detailed comlexity analysis of the problem of the development of intelligent EIS for decision support.